1995
DOI: 10.1021/j100002a015
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Fluorescence of Molybdenocene and Tungstenocene in Low-Temperature Matrixes

Abstract: The reactive metallocenes, tungstenocene and molybdenocene (M($-CsH5)2; M = Mo, W), have been generated by photolysis of the corresponding dihydnde complexes, M($-C~H~)ZHZ, in argon and nitrogen matrices at 12 K. The metallocenes have been probed by laser-induced fluorescence with a pulsed tunable laser and by UV/vis absorption spectroscopy. Structured emission is observed from the LMCT excited states (lifetimes 10 ns). The spectra are complicated by multiple sites/conformers, but emission spectra of a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…Studies of the photochemistry of Cp 2 W­(H) 2 in low-temperature matrices , confirmed the formation of the [Cp 2 W] fragment by H 2 photoinduced concerted elimination; [Cp 2 W] was characterized by IR and UV/vis absorption, laser-induced fluorescence, , and magnetic circular dichroism , (see section for details).…”
Section: Metal Hydride Photochemistry By Transition Metal Groupmentioning
confidence: 88%
See 2 more Smart Citations
“…Studies of the photochemistry of Cp 2 W­(H) 2 in low-temperature matrices , confirmed the formation of the [Cp 2 W] fragment by H 2 photoinduced concerted elimination; [Cp 2 W] was characterized by IR and UV/vis absorption, laser-induced fluorescence, , and magnetic circular dichroism , (see section for details).…”
Section: Metal Hydride Photochemistry By Transition Metal Groupmentioning
confidence: 88%
“…Matrix isolation experiments revealed tungstenocene as the primary photoproduct and showed via IR, UV–vis, laser-induced fluorescence, and magnetic circular dichroism that it has a parallel sandwich structure with a 3 E 2g ground state. These early experiments are summarized in reviews. , Since then, the matrix photochemistry has been investigated in more detail. Additional reports have added the photochemical reactions of Cp 2 W­(H) 2 in solution with HSiCl 3 , HSiMe 2 Cl, and HSiMe 3 to make the corresponding Cp 2 WH­(SiR 3 ) complexes. , Co-irradiation of Cp 2 W­(H) 2 and metal–metal-bonded carbonyl complexes such as [CpNi­(CO)] 2 or [CpRu­(CO) 2 ] 2 have been used to generate heterodinuclear complexes. In these reactions with two metal complexes, there is no control of which complex undergoes photochemical reactions, and it is likely that both contribute .…”
Section: Photochemical Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…10-2 and 10-1 respectively (photolysis at 366 nm, ref 15). More recently, Belt et a1 exploited the knowledge of the extinction coefficient of the primary photoproduct of Ru to obtain a quantum yield for loss of hydrogen from Ru(drnpe)zHz of 0.85 k 0.05 via time-resolved spectroscopy (photolysis at 308 nm, ref 16). However, there is no knowledge of the variation of the quantum yield with wavelength of photolysis.…”
Section: Steady State Studies Of Photochehlical Elimination Of Hydrogenmentioning
confidence: 99%
“…2,3 These unstable metallocenes were formed by UV photolysis of the corresponding (di)hydride precursors. Vibrationally resolved emission and excitation spectra were recorded for each complex with tunable pulsed laser irradiation.…”
Section: Introductionmentioning
confidence: 99%